(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to present the concept of intangible assets and discuss the foundations of their measurement and valuation according to the IAS 38 and IVS 210 standards, as well as the IFRS 13 standard, which is directed to be used in the event of re-valuating intangible assets according to IAS 38, and knowing the value of the economic unit through the Tobin’s Q scale and explaining the impact of the above on the value of the economic unit. One of the most important findings of the research is that, despite the difference in measurement guidelines between IAS 38 and IVS 210, there was no statistically significant effect of measuring intangible assets on the value of the economic unit, regardless of whether it was measured according to IAS 38 or IVS 210. The research also recommended the need for the economic unit, the research sample, to provide additional information about intangible assets in its reports, such as their history and the extent of their importance to achieving the success and continuity of the unit, to provide a better understanding of the extent to which these assets affect the value of the economic unit.